Urinary Stents 2022
DOI: 10.1007/978-3-031-04484-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles. Potential for Use to Prevent Infections

Abstract: One of the major issues related to medical devices and especially urinary stents are infections caused by different strains of bacteria and fungi, mainly in light of the recent rise in microbial resistance to existing antibiotics. Lately, it has been shown that nanomaterials could be superior alternatives to conventional antibiotics. Generally, nanoparticles are used for many applications in the biomedical field primarily due to the ability to adjust and control their physicochemical properties as well as thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…A study showed that the modification of commercial PVC with methylene blue and 2 nm AuNPs upon exposure to red laser light for 4–8 min increased the photosensitivity of pathogens S. epidermis and E. coli ( Noimark et al., 2012 ). Aegle marmelos leaf extract capped with AuNPs has antimicrobial activity against various biofilm-forming organisms on urinary catheters ( Table 3 ) ( Sánchez et al., 2021 ; Filipović et al., 2022 ).…”
Section: Antimicrobial Coatings and Impregnationmentioning
confidence: 99%
“…A study showed that the modification of commercial PVC with methylene blue and 2 nm AuNPs upon exposure to red laser light for 4–8 min increased the photosensitivity of pathogens S. epidermis and E. coli ( Noimark et al., 2012 ). Aegle marmelos leaf extract capped with AuNPs has antimicrobial activity against various biofilm-forming organisms on urinary catheters ( Table 3 ) ( Sánchez et al., 2021 ; Filipović et al., 2022 ).…”
Section: Antimicrobial Coatings and Impregnationmentioning
confidence: 99%